Hydrogenation of Olefins, Alkynes, Allenes, and Arenes by Borane-Based Frustrated Lewis Pairs - Wech, Felix; Gellrich, Urs (Synthesis, 2021)
In recent years, borane-based frustrated Lewis pairs have proved to be efficient hydrogenation catalysts and they have become an alternative to transition-metal-based systems. The hydrogen activation by classic FLPs leads to a protonated Lewis base and a borohydride. Consequently, hydrogenations catalyzed by classic FLPs consist of stepwise hydride transfer reactions and protonations (or vice versa). More recently, systems that operate via an initial hydroboration have allowed the substrate scope for FLP-catalyzed hydrogenations to be extended. In this review, hydrogenations of organic substrates catalyzed by borane-based frustrated Lewis pairs are discussed. Emphasis is given to the mechanistic aspects of these catalytic reactions.1 Introduction2 FLP-Catalyzed Hydrogenation of Polarized Double Bonds2.1 Hydrogenation of Michael Acceptors by FLPs2.2 Asymmetric Hydrogenation of Polarized Double Bonds2.3 Hydrogenation of Arenes and N-Heterocycles3 Hydrogenation of Unactivated Olefins and Alkynes3.1 Hydrogenation of Olefins and Alkynes by an Initial Hydroboration4 Summary and Outlook
Keywords: frustrated Lewis pair; hydrogenation; hydrogen activation; hydroboration; pyridone–borane; metal-free catalysis